THE IMPАCT OF REMOTE WORK ON EMPLOYEE PRODUCTIVITY АND JOB SАTISFАCTION - Khurshid Mаrdonov Isomiddin ogli (Bright Mind Publishing, 2025)
This article examines the impact of online work on employee productivity, particularly in the case of brokers and dispatchers working in the logistics sector. Three participants, Mike, Allan and George, share their real-life experiences of online work, discussing the main tasks, time management, work challenges and factors that affect productivity, as well as how they manage work-life balance. In addition, it is conducted using thematic analysis. It also provides information on how psychological and some technical issues affect employee performance.
Keywords: Remote work, logistics, brokerage, work efficiency, employee health, time management, stress, work-life balance.